2017
DOI: 10.1080/23723556.2017.1299274
|View full text |Cite
|
Sign up to set email alerts
|

Caspase 2 in mitotic catastrophe: The terminator of aneuploid and tetraploid cells

Abstract: Mitotic catastrophe is an oncosuppressive mechanism that targets cells experiencing defective mitoses via the activation of specific cell cycle checkpoints, regulated cell death pathways and/or cell senescence. This prevents the accumulation of karyotypic aberrations, which otherwise may drive oncogenesis and tumor progression. Here, we summarize experimental evidence confirming the role of caspase 2 (CASP2) as the main executor of mitotic catastrophe, and we discuss the signals that activate CASP2 in the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 31 publications
(43 reference statements)
1
21
0
Order By: Relevance
“…5e ). In support of these results, western blotting showed that MASTL depletion increased cleaved-PARP and γ-H2AX, and activated caspase-2, as evidenced by the decrease in procaspase-2, which is a major caspase in the mitotic cell death in response to DNA damage [ 7 ], and decreased phosphorylated ENSA, a substrate of MASTL, in a time-dependent manner in MCF7 and T47D cells (Fig. 5f ).…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…5e ). In support of these results, western blotting showed that MASTL depletion increased cleaved-PARP and γ-H2AX, and activated caspase-2, as evidenced by the decrease in procaspase-2, which is a major caspase in the mitotic cell death in response to DNA damage [ 7 ], and decreased phosphorylated ENSA, a substrate of MASTL, in a time-dependent manner in MCF7 and T47D cells (Fig. 5f ).…”
Section: Resultssupporting
confidence: 57%
“…Mitotic catastrophe is a type of cell death that results from abnormal mitosis following DNA damage, such as that caused by irradiation, and is related to premature chromosome condensation and the formation of large cells with multiple micronuclei [ 5 , 6 ]. DNA damage-induced mitotic catastrophe can be driven by the activation of caspases, particularly caspase-2 [ 6 , 7 ]. Recently, it was shown that the activation of caspase-2 in response to DNA damage plays an oncosuppressive role through the reduction of genomic instability and chromosomal aberrations that may promote tumorigenesis [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are nine genes annotated as being involved in apoptosis, a process that can be initiated if a cell fails a mitotic check point. CASP2, long considered to be an orphan caspase 72 , is recognised as a key factor in driving cell apoptosis (mitotic catastrophe) triggered by mitotic abnormalities, such as defects in chromosomes, mitotic spindles, or the cytokinesis apparatus 73,74 . Other genes within the list await functional validation.…”
Section: Discussionmentioning
confidence: 99%
“…These round of polyploidy engender defective mitosis and non-viable aneuploid daughter cells that die by the activation of the mitochondrial pathway of cell death. This particular death is called mitotic catastrophe 38,40,41 . We found similar results using the neuroblastoma cell lines SK-N-F1, SK-N-AS, IMR32, SK-N-RA and SK-N-DZ treated with Reversine or Mps-BAY2a.…”
Section: Mps1 Inhibition Provokes the Mitochondrial Pathway Of Apoptomentioning
confidence: 99%